Virtual Screening of Natural Compounds Against Six Protein Receptors Coded by The SARS-CoV-2 Genome - Fikry Awaluddin; Irmanida Batubara; Setyanto Tri Wahyudi (Universitas Jenderal Soedirman, 2023)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is the virus that causes Coronavirus 2019 (COVID-19). To date, there has been no proven effective drug for the treatment or prevention of COVID-19. A study on developing inhibitors for this virus is carried out using molecular docking simulation methods. 3CL-Pro, PL-Pro, Helicase, N, E, and M protein were used as protein targets. Autodock Vina, Autodock 4.2, and PSOVina were used in this study. This study aims to obtain a model of ligands interactions of active natural compounds against the receptor protein encoded by the SARS-CoV-2 genome and their free binding energy to propose active compounds from natural products that have potential as a drug for COVID-19. Corilagin (-14,42 kcal/mol), Scutellarein 7-rutinoside (-13,2 kcal/mol), Genistein 7-O-glucuronide (-10,52 kcal/mol), Biflavonoid-flavone base + 3O (-11,88 and -9,61 kcal/mol), and Enoxolone (-6,96 kcal/mol) has the best free energy value at each protein target indicating that the compound has the potential as a viral protein inhibitor for further investigation. This research is limited to computer simulations, where the results obtained are still a prediction.